2017
DOI: 10.1371/journal.pone.0183687
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Helicobacter pylori infection and peptic disease with diabetic mellitus: Results from a large population-based study

Abstract: BackgroundEvidence is conflicting regarding the association between Helicobacter pylori infection and diabetes mellitus. The study objective was to examine associations of H. pylori infection, gastric ulcers and duodenal ulcers, with diabetes mellitus.MethodsThis cross-sectional study was undertaken using coded data from the computerized database of Maccabi Health Services in Israel, on 147,936 individuals aged 25–95 years who underwent the urea breath test during 2002–2012. Multiple logistic regression models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 44 publications
0
13
0
3
Order By: Relevance
“…MHS is ranked as the second largest HMO in Israel, insuring about two million people, i.e., about one-quarter of the population. The study cohort has been described in detail 32 . Briefly, we accessed deidentified information of persons aged 25 years or older who underwent UBT during 2002–2012.…”
Section: Methodsmentioning
confidence: 99%
“…MHS is ranked as the second largest HMO in Israel, insuring about two million people, i.e., about one-quarter of the population. The study cohort has been described in detail 32 . Briefly, we accessed deidentified information of persons aged 25 years or older who underwent UBT during 2002–2012.…”
Section: Methodsmentioning
confidence: 99%
“…28,29 The study included data of adults aged 25-95 years who performed the urea breath test (UBT) between 2002 and 2012. MHS HMO has two million insured persons, corresponding to ~25% of the population in Israel.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Details on the study cohort were described elsewhere. 28,29 The study included data of adults aged 25-95 years who performed the urea breath test (UBT) between 2002 and 2012.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…The burden ensuing from H. pylori infection is enormous. Haj et al (2017) revealed that H. pylori causes persistent gastritis and small intestine ulcers, and in uncommon events gastric malignant growth and lymphoma, that typically develop throughout adulthood. Many studies have addressed the link between H. pylori infection and diabetes mellitus (DM), a medical condition ensuing from either duct gland not producing enough hypoglycemic agent, or cells of the body improperly responding to the insulin created as reported by Awuchi et al (2020).…”
Section: The Burden Of H Pylori Infectionmentioning
confidence: 99%
“…Gastric irritation and damage to the gastric tissue layer can be at the bottom of a relationship between H. pylori disease and diabetes mellitus. However, the role of peptic ulcerations, that develop following persistent internal organ inflammation in DM, has seldom been assessed (Haj et al, 2017).…”
Section: The Burden Of H Pylori Infectionmentioning
confidence: 99%